Investigating Bering Sea oceanographic response to the Milankovitch orbital cycle climatic shift during the middle Pleistocene - Worne, Savannah (2020)
The transition of Earth’s glacial-interglacial cycles from 41 kyr to 100 kyr periodicity during the middle Pleistocene (the Mid-Pleistocene Transition (MPT); ~1.2–0.6 Ma) marks one of the largest climate events of the Cenozoic, but the causes of this cooling transition remain unclear, as the emergence of the 100 kyr Milankovitch orbital ‘eccentricity’ in climate records occurred without a long term change in external orbital forcing. Hypotheses for this transition have so far remained largely untested due to a lack of detailed, high resolution climate proxy information from critical regions on the planet. Major hypotheses infer changes to North American Ice Sheet dynamics, an early expansion of subpolar sea ice, and decreasing atmospheric CO2. Using sediment geochemistry and palaeontological proxies, this thesis assesses how the variability in sea ice, nutrient upwelling and primary productivity in the Northern Bering Sea impacted regional and global climate through the MPT, via their impact on North Pacific Intermediate Water expansion, regional carbon cycling and the subpolar biological pump.